Integration of logistics system departments - Горяинов, Алексей Николаевич; Бакуменко, Юлия Александровна (Eastern-European Journal of Enterprise Technologies, 2009)
The problems of the relationship between the spheres and areas of integration are shown. Integration coefficient characterizing the captives to pound some logistics functions between the departments of enterprises is proposed